The great moderation in the euro area : what role have macroeconomic policies played - Cabanillas, Laura Gonzalez; Ruscher, Eric.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission: Directorate-General for Economic and Financial Affairs, 2008)
Most OECD countries have experienced a sharp reduction in the volatility of output and inflation over the past three decades. Although this Great Moderation process has stirred considerable interest in economic and policy circles, research on its causes has so far tended to focus on the US economy and has produced relatively little empirical evidence on the euro area or other non-US OECD countries. This paper contributes to fill in the gap by providing a euro-area view of the Great Moderation process and by assessing the euro-area experience against developments in other OECD countries. Its main focus is on the possible role of macroeconomic policies. After reviewing a set of key stylised facts of the fall in output growth volatility in the euro area, the paper discusses the possible channels through which economic policies may have contributed to the Great Moderation and resents the results of an econometric panel analysis of the determinants of output growth volatility. Its main conclusion is that the Great Moderation is not just the result of a long period of luck in the form of milder shocks but can also partly be ascribed to changes in economic policies, in particular improvements in the conduct of monetary policy and, to a lesser extent, more powerful automatic fiscal stabilisers.
Economic Papers.